Linking longitudinal cohort data with administrative records to test whether school readiness predicts adolescent mental health problems - Wertz, Jasmin; Zeng, Lijie (International Journal of Population Data Science, 2025)
Objective Mental health problems are among the most common and debilitating health conditions in young people. Early identification is key to make support available in a timely manner. We combined administrative and longitudinal cohort study data from England to test whether routinely collected school data could aid in population-wide screening efforts. Method Data came from the UK Millennium Cohort Study (MCS), a longitudinal birth cohort study of children born between 2000-2002. Cohort data was linked the National Pupil Database, with successful linkage for n=8,671 children attending primary school in England. School readiness was measured using the Early Years Foundation Stage Profile when children were 4-5 years old. The profile is based on teacher reports of children’s personal/emotional/social development; communication and language; numeracy, literary, physical development; understanding of the world; and creative development. Mental health problems were measured through parent report at ages 11, 14 and 17, and adolescent self-report at age 17. Results Children rated as achieving less than ‘good’ school readiness at age 4-5 were at greater risk of experiencing a parent-reported mental health problem in adolescence, compared to children rated as achieving ‘good’ school readiness. School readiness had incremental predictive value over and above children’s demographic information that schools routinely collect, including relative age within class, ethnicity, household and area deprivation at age 5; as well as children’s special educational needs and disabilities at age 5. Children’s development in most domains of school readiness predicted mental health problems, including in areas that have not been studied much in previous research (such as creative development). Although school readiness predicted both externalising and internalising problems, associations tended to be larger for externalising problems. Conclusion Our findings illustrate how routinely collected school data could be used to improve the prediction of young people’s mental health problems at a population level, to inform prevention and treatment planning. The findings also illustrate the potential of administrative data to advance research on the development of psychopathology.